2004
DOI: 10.1002/ijc.20764
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for a link between silica dust and esophageal cancer

Abstract: Our objective was to examine the relationship between silicosis and esophageal cancer in Hong Kong. The mortality of esophageal cancer was investigated among caisson and non-caisson workers in a cohort of 2,789 male silicotic workers in Hong Kong during the period 1981-99. The standardized mortality ratio (SMR) was calculated using the Hong Kong general population rates as reference. The indirect method proposed by Axelson was used to adjust for the confounding effects of cigarette smoking and alcohol drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Other studies have also found an association with silica dust, which may give some support to our results 2426. Whether the increase in risk of OC for this occupational group is real or not (ie, is due to incomplete control of the confounders tobacco smoking and alcohol drinking) is a question that should be clarified by further studies.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have also found an association with silica dust, which may give some support to our results 2426. Whether the increase in risk of OC for this occupational group is real or not (ie, is due to incomplete control of the confounders tobacco smoking and alcohol drinking) is a question that should be clarified by further studies.…”
Section: Discussionsupporting
confidence: 85%
“…However, several studies have suggested that occupational exposure to asbestos could increase EC risk between 2-fold and 16-fold [241245]. Other studies have found increased EC risk in relation to occupational exposure to silica [246249]. However, other studies have shown no or only very slight increased risk with these occupational exposures.…”
Section: Occupational Exposurementioning
confidence: 99%
“…Other risk factors, such as Barrett's esophagus and occupational exposure to silica dust, 8,33 are likely in the etiology of esophageal cancer. However, to date, evidence on these aspects is very sparse and in demand.…”
mentioning
confidence: 99%